Gamifikáció a hitoktatásban - SZÉNÁSI, Lilla; SZÉNÁSI, Levente (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2023)
Gamification in Religious Education In its first part, the study describes what definitions were created to define the notion of “game” and what characteristics of it can be observed. The second part shows the place of game itself in religious education, and the reason why it is useful if included in the practice of religious education. The third part revolves around the concept of gamification and points out the differences between games and gamification. The fourth part deals with the applicability of gamification in religious education, in which, in addition to theory, practice also appears. The two authors would like to answer the questions raised in the study Possible Forms of Gamification in School Catechesis published in 2019. On the one hand, with the involvement of the young people of the Reformed Church in Martos, who are preparing for confirmation, the Text Eater program (application) designed for them, which tries to facilitate learning the answers to the questions of the Catechism, is evaluated based on practice. On the other hand, with the involvement of the pupils of the Reformed Elementary School with Hungarian as the Language of Instruction in Martos, the gamification evaluation is assessed pertaining to its use in religious education, as a second potential gamification tool.